Patient Portal Activation Disparities by Ward, Census Tract, and Zip Code in an Urban Landscape Among Neurology Patients: Cross-Sectional Multi-Scale Analysis - Nicholas Streicher (Journal of Medical Internet Research, 2026)
Abstract Background Patient portals are essential infrastructure, reinforced by the 21st Century Cures Act, yet adoption remains inequitable. The COVID-19 pandemic accelerated portal adoption as telehealth and remote result delivery made electronic access integral to care, but racial and ethnic disparities persisted. Understanding activation determinants is critical for addressing digital health disparities, particularly among neurology patients, for whom cognitive, speech, and mobility impairments can complicate portal use. Objective We examined the demographic, geographic, and neighborhood-level factors associated with patient portal activation among neurology patients in the Washington, DC (officially the District of Columbia), metropolitan area. Methods We conducted a cross-sectional study of 72,417 patients with at least one outpatient neurology encounter (including telehealth) at 2 academic medical centers sharing a common electronic health record in Washington, DC. The primary outcome was portal activation, defined as having logged into the portal at least once. We examined associations using multivariable logistic regression (reporting adjusted odds ratios [aORs]) adjusting for age, sex, race and ethnicity, visit counts, and year of most recent encounter, and we assessed geographic patterning at multiple scales (the DC metropolitan catchment area, DC’s 8 wards, census tracts via geocoded addresses, and residential zip codes) using Pearson and Spearman correlations between ward- and tract-level American Community Survey indicators and activation. Results Portal activation was 64.7% (46,851/72,417) overall; patients averaged 9.7 (SD 18.9) visits. Activation varied by race and ethnicity (non-Hispanic White: 21,420/28,154, 76.1%; non-Hispanic Asian: 1109/1925, 57.6%; non-Hispanic Black: 13,057/22,900, 57%; Hispanic: 1979/3600, 55%). In adjusted models, odds of activation were lower for non-Hispanic Black (aOR 0.46, 95% CI 0.44‐0.48), Hispanic (aOR 0.34, 95% CI 0.31‐0.37), and non-Hispanic Asian (aOR 0.47, 95% CI 0.42‐0.52) patients vs non-Hispanic White patients, and each SD increase in age was associated with lower odds (aOR 0.60, 95% CI 0.59‐0.61; P